P-wave velocity structure of the ice sheet and the shallow crust beneath the Mizuho traverse route, East Antarctica, from seismic refraction analysis - Tsutsui, Tomoki; Murakami, Hiroshi; Miyamachi, Hiroki; Toda, Shigeru; Kanao, Masaki (National Institute of Polar Research, 2001)
P(論文) A seismic survey with a high density network was conducted by the 41st Japanese Antarctic Research Expedition (JARE-41) in the austral summer of 1999-2000. The seismic line was 190 km long, along the Mizuho traverse route from the base camp S16. 160 temporary seismic stations using data loggers were installed. The first arrival times were analyzed by the refraction method. The structure of the upper crust and overlying ice-sheet are revealed down to 7 km from refraction analysis of the first arrival times. A three layered structure is estimated. The first layer with a velocity of 3.8 km/s appears to be ice-sheet. The second layer with a velocity of 6.2 km/s of P-wave velocity is the surface layer of the continental crust. The thickness of this second layer is estimated to be approximately 5 km. The third layer is defined by the P-wave velocity of 6.5 km/s. Its shape of the upper interface is not declared. The topography of the basement determined from seismic refraction matches well with that determined from ice-radar sounding except for a small difference in the estimated depth of the basement. Two abrupt changes of the second layer depth are found near shot S-1 and shot S-4. The former includes a velocity change in the second layer. The latter discontinuity corresponds to the echo-less points of the ice-radar sounding. Velocity changes in the first and second layers are not detected across the latter discontinuity. departmental bulletin paper